Peran Musyrif dalam Mendisplinkan Santri di Pondok Pesantren Tahfidzul Qur'an - Santoso, Joko; Subando, Joko (Lembaga Yasin AlSys, 2026)
Student discipline is a crucial element in supporting the success of tahfidz Al-Qur’an programs because it requires time consistency, orderly worship, and compliance with Islamic boarding school regulations; therefore, a supervisory figure is needed to guide and oversee this discipline-building process systematically. This study aimed to describe the role of musyrif in disciplining students in tahfidzul Qur’an Islamic boarding schools and to examine the strategies and factors that influence the effectiveness of such disciplinary guidance. The study employed a descriptive qualitative approach, with data gathered through a literature review and conceptual analysis of disciplinary guidance practices in tahfidz Islamic boarding schools. The findings indicate that musyrif play strategic roles as mentors, supervisors, and role models in instilling disciplinary values through exemplification, habituation, intensive supervision, religious advice, and the provision of educational sanctions and appreciation. The success of student discipline guidance is influenced by students’ internal factors, the pesantren environment, the role-modelling of musyrif, and the institutional system and culture of discipline. The study concludes that strengthening the role of musyrif consistently and sustainably is key to shaping student discipline as an integral part of Islamic character education in tahfidz Islamic boarding schools.